2022
DOI: 10.1136/thoraxjnl-2021-218461
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) and cervical dysplasia in adult female cystic fibrosis (CF) lung transplant recipients

Abstract: Human papillomavirus (HPV) is the principal risk factor for cervical cancer. Transplant recipients are at a disproportionate risk of HPV complications. We conducted a single-centre, retrospective study of adult female cystic fibrosis (CF) lung transplant recipients between 2008 and 2021. We observed 12 of 34 (35.3%) with ≥1 abnormal pap smear (median age: 26.7 years). Complications included refractory anogenital warts (n=3), vulvectomy (n=2) and cervical cancer (n=4), with two deaths from metastatic disease. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Majority of the participants were WLWH, indicating the importance of studying HPV infection in this particular group. It is well-established that individuals with compromised immune systems, such as WLWH, are at a higher risk of acquiring HPV infection and developing associated complications, including cervical cancer [ 1 , 50 52 ]. By including a substantial number of WLWHIV in our study, we have shed light on an important aspect of HPV epidemiology within the Zambian context.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the participants were WLWH, indicating the importance of studying HPV infection in this particular group. It is well-established that individuals with compromised immune systems, such as WLWH, are at a higher risk of acquiring HPV infection and developing associated complications, including cervical cancer [ 1 , 50 52 ]. By including a substantial number of WLWHIV in our study, we have shed light on an important aspect of HPV epidemiology within the Zambian context.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the participants were WLWH, indicating the importance of studying HPV infection in this particular group. It is well-established that individuals with compromised immune systems, such as WLWH, are at a higher risk of acquiring HPV infection and developing associated complications, including cervical cancer 1,5153 . By including a substantial number of WLWHIV in our study, we have shed light on an important aspect of HPV epidemiology within the Zambian context.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…But it also brings new challenges and burdens, including ongoing commitment to intensive follow-up and demanding drug regimens with a range of new adverse effects. Thornton et al have highlighted an important but perhaps overlooked consequence of the immune suppression necessary after lung transplantation—that of cervical dysplasia caused by human papilloma virus (HPV) 1. In a single-centre retrospective study, they reported high rates of HPV-associated morbidity in women with CF who had undergone lung transplant, and a 4 x greater risk of cervical dysplasia compared with non-transplanted CF controls.…”
mentioning
confidence: 99%